Development and Validation of Producer and Consumer Preference Models for Rice Varieties in Bangladesh - Hossain, Md Ismail; Rahman, Niaz Md Farhat; Kabir, Md Shahjahan; Siddique, Md Abu Bakr; Tareq, Muhammad (Bangladesh Rice Journal, 2015)
Rice production depends on both producers and consumers preference. The consumption of rice depends on consumers taste and habits. The objectives of this study were to develop and validate mathematical models for producers, consumers and producers-cum-consumers preference to rice varieties and to evaluate the factors affecting both producers and producer-cum-consumers decision on varieties for rice cultivation and can provide an indication of the factors affecting consumers preferences to rice varieties in Dhaka, Gazipur, Dinajpur and Bhola districts of Bangladesh. Chi-square (X2) tests were used to explore the significant difference of preferring rice varieties among the groups of people and compared the results with the proposed models for validation. Producers and producers-cum-consumers preferred BR11, BR22 and BRRI dhan32 in T. Aman; BR16, BRRI dhan28 and BRRI dhan29 in Boro and BR9, BR16 and BR20 in Aus seasons respectively. The specific grain quality characteristics such as whiteness, brokens, shape, amylose (%), aroma, cooking quality, hardness and chalkiness influenced the consumers and producers preference. Furthermore, pure consumers also preferred rice varieties on the basis of its tastiness and fineness. Bangladesh Rice j. 2015, 19(1): 63-71